2022
DOI: 10.1177/10600280221132851
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Versus Methylnaltrexone for Opioid-Induced Constipation in Critically Ill Patients

Abstract: Background: Opioid-induced constipation (OIC) may occur in up to 81% of critically ill patients and can lead to many complications. Opioid antagonists are a reasonable approach and may be used for managing OIC. Objective: The purpose of this study was to assess the efficacy of enteral naloxone (NLX) versus subcutaneous methylnaltrexone (MNTX) for the management of OIC in critically ill patients. Methods: A retrospective analysis was conducted on adult patients who received NLX or MNTX and a continuous opioid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The final selection included 9 papers: two randomized controlled trials, 19,20 one prospective case‐series, 21 three retrospective case‐series 22–24 and three case reports 25–27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final selection included 9 papers: two randomized controlled trials, 19,20 one prospective case‐series, 21 three retrospective case‐series 22–24 and three case reports 25–27 …”
Section: Resultsmentioning
confidence: 99%
“…The final selection included 9 papers: two randomized controlled trials, 19,20 one prospective case-series, 21 three retrospective case-series [22][23][24] and three case reports. [25][26][27] Tables 3 and 4 report the study characteristics and the main outcomes.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, a retrospective evaluation by Habeeb et al 11 showed a faster time to BM with naloxone than MNTX (18 vs 41 hours). In keeping with studies by Merchan et al and Habeeb et al, the median time to BM and number of BMs in 72 hours were also investigated in this study.…”
Section: Discussionmentioning
confidence: 99%